Pengaruh Pembelajaran Jarak Jauh dan Peran Orang Tua terhadap Prestasi Belajar PAI - Ikke Nurjanah; Abdullah Hadziq (Fahima, 2022)
Distance Learning is the best solution that the world of education can do today to avoid spreading the COVID-19 virus and its variants. By implementing distance learning, it is hoped that students will listen to material explanations from the teacher and actively participate in learning activities in the form of finding sources of information from other media. This study aims to determine the effect of distance learning and the role of parents on PAI learning achievement for class VIII SMP Negeri Mojogedang Karanganyar Regency for academic year 2020/2021. The hypothesis proposed is that distance learning and the role of parents have a significant effect on PAI learning achievement for class VIII SMP Negeri Mojogedang Karanganyar Regency for academic year 2020/2021. This type of research is quantitative descriptive with data collection methods through questionnaires, observations, interviews, and documentation. The research subjects were eighth-grade students of SMP Negeri 2 Mojogedang with a population of 260, and a sample of 116 students was taken. The results of the study show that: distance learning has a positive and significant effect on PAI learning achievement for class VIII students of SMP Negeri 2 Mojogedang Karanganyar for academic year 2020/2021; the role of parents has a positive and significant impact on PAI learning achievement for grade VIII students of SMP Negeri 2 Mojogedang, Karanganyar Regency for academic year 2020/2021; distance learning and the role of parents have a positive and significant effect on PAI learning achievement for class VIII students of SMP Negeri 2 Mojogedang, Karanganyar Regency for academic year 2020/2021.